Atividade antibacteriana e antibiofilme de complexos de sulfa e ouro contra bactérias gram-negativas e gram-positivas - Mizdal, Caren Rigon (2018)
Antibiotic resistance develops as a natural consequence of the bacterial population's ability to adapt. In addition, the indiscriminate use of antibiotics has been considered as one of the factors that predispose the increase of bacterial resistance. It is known that one reason for the difficulty of treating these infections is due to the fact that they are caused by biofilms, since this strategy allows the adhesion of microorganisms to plastic and smooth surfaces, such as catheters, heart valves and prostheses, preventing action of antimicrobials and even of phagocytic cells to the focus of infection. Although antibiotic therapy currently used to treat infections is broad-spectrum, the emergence of antibiotic-resistant strains is rapidly depleting the available treatment options. The rise in antibiotic-resistant infections continues to plague health care, meanwhile there is a decline in research and development of new antibiotics to deal with this threat. Thus, it is important to seek effective alternatives against pathogenic microorganisms. In this work the objective was to evaluate the antimicrobial activity and antibiofilm of compounds from the complexation of sulphonamides with gold on strains of Staphylococcus aureus and Pseudomonas aeruginosa. The antimicrobial activity was evaluated by conventional methods on standard strains and clinical isolates of S. aureus and P. aeruginosa. The index of Fractional Inhibitory Concentration was performed using the Checkerboard method. Cell viability was also assessed through the growth curve. Inhibition of biofilm formation was performed by microtiter plate assay and the formed biofilm was evaluated by confocal microscopy. The toxicity of the compounds was analyzed by the Caenorhabditis elegans assay. Analysis of the motility of P. aeruginosa against the compounds was also performed. Virtual screening was performed using the AutoDock Vina program on the P. aeruginosa LasR protein. The articles published confirmed the excellent antimicrobial activity and antibiofilm of the sulfamethoxasol compounds against Gram-positive bacteria; S. aureus and Gram-negative; P. aeruginosa. Likewise, they showed excellent activity in cell viability and did not present toxic effects. The computational simulation allowed to predict the value of the interaction energy between the protein and the compounds. The results indicated that the sulfonamide compounds may be promising for reducing the formation of biofilms by stimulating further investigations aiming the insertion of the sulfonamide compounds as novel antibacterial agents.